ANALISA PEMERINTAHAN SUMATERA BARAT TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI - Hery Haryanto; Junestin Junestin; Andriani Fahira; Chairunisa Aj Reqha; Putri Surya Sri Rahayu; Nancy Nancy (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Inflation, unemployment, and economic growth are indicators of macroeconomics where macroeconomics is the study of economic activity in a country or region. This analysis will focus on unemployment after rising inflation in a province in Indonesia. The subject of the analysis chosen was West Sumatra, which is one of the provinces that has a fairly high unemployment rate in Indonesia. The research methods used are qualitative and quantitative techniques, the data that will be used later are unemployment rate data, inflation data and government policies. The purpose of this study is to find out how much the increase in unemployment from 2019 to 2020 occurred in one of the provinces in Indonesia, namely West Sumatra.